The rise of bronze in Central Asia: new evidence for the origin of Bronze Age tin and copper from multi-analytical research - Berger, Daniel; Kaniuth, Kai; Boroffka, Nikolaus; Brügmann, Gerhard; Kraus, Steffen; Lutz, Joachim; Teufer, Mike; Wittke, Andreas; Pernicka, Ernst (Frontiers in Earth Science, 2023)
The Bronze Age in Central Asia was dominated by the Andronovo Culture and the Bactria-Margiana Archaeological Complex (BMAC). Both cultural entities produced bronze, however, the extent of bronze production and use varied considerably in space and time across their territories. The introduction and spread of bronze metallurgy in the region is commonly associated with the Andronovo Culture, but comparatively little is known about the copper and tin sources that were exploited to make the bronze. To shed light on this aspect, this paper examines 91 bronze artefacts from the Middle Bronze Age (MBA) and the Late Bronze Age (LBA) recovered from twenty sites of Andronovo and the BMAC through a combined evaluation of chemical and isotopic analyses. Trace element patterns and isotopic compositions of lead, tin, and copper are determined for the objects complemented by tin isotope analysis of Central Asian tin ores. The data shows a clear separation of two source areas in the MBA and LBA I: the BMAC obtained copper from polymetallic (tin-bearing) deposits in Iran (Deh Hosein, Nakhlak/Bagh Gorogh) and possibly Afghanistan, while the Andronovo Culture mainly used copper from the Tian Shan Mountains. With the transition to the LBA II, a change in the material basis can be recognised, in which the BMAC increasingly relied on metal deposits from the Andronovo territory. The most important result in this context is the analytical proof of the coextraction of copper and tin from the copper-tin mine at Mushiston, Tajikistan, and the first direct link of tin in bronze objects with a tin deposit. Mushiston apparently supplied both cultural macro regions with a “natural” bronze, which accounted for about one third of all objects analysed, but there is no indication yet that metal or ores from Mushiston were traded or used at a distance of more than 500 km. Moreover, the artefact data indicates a decline in the exploitation of the mine in the course of the developed LBA, while other copper and tin sources in the Tian Shan and probably the Hindukush were exploited. This testifies to the intensive use of the rich mineral resources of Central Asia and beyond, as well as the intensification of cultural and trade contacts between Andronovo and the BMAC.